Macromolecular Design Strategies for Preventing Active‐Material Crossover in Non‐Aqueous All‐Organic Redox‐Flow Batteries. Issue 6 (10th January 2017) - Doris, Sean E.; Ward, Ashleigh L.; Baskin, Artem; Frischmann, Peter D.; Gavvalapalli, Nagarjuna; Chénard, Etienne; Sevov, Christo S.; Prendergast, David; Moore, Jeffrey S.; Helms, Brett A.
Abstract: Intermittent energy sources, including solar and wind, require scalable, low‐cost, multi‐hour energy storage solutions in order to be effectively incorporated into the grid. All‐Organic non‐aqueous redox‐flow batteries offer a solution, but suffer from rapid capacity fade and low Coulombic efficiency due to the high permeability of redox‐active species across the battery's membrane. Here we show that active‐species crossover is arrested by scaling the membrane's pore size to molecular dimensions and in turn increasing the size of the active material above the membrane's pore‐size exclusion limit. When oligomeric redox‐active organics (RAOs) were paired with microporous polymer membranes, the rate of active‐material crossover was reduced more than 9000‐fold compared to traditional separators at minimal cost to ionic conductivity. This corresponds to an absolute rate of RAO crossover of less than 3 μmol cm −2  day −1 (for a 1.0 m concentration gradient), which exceeds performance targets recently set forth by the battery industry. This strategy was generalizable to both high and low‐potential RAOs in a variety of non‐aqueous electrolytes, highlighting the versatility of macromolecular design in implementing next‐generation redox‐flow batteries. Abstract : Better sieving through chemistry : Macromolecular chemistry provides a general approach for blocking redox‐active organic molecules from crossing through battery membranes at minimal cost to ionic conductivity. This advance solves a critical challenge facing next‐generation redox‐flow batteries, clearing the way toward efficient, low‐cost grid‐scale energy storage.